Evaluation of Geotechnical and Structural Performance of Cement-Stabilized Soil with Saw Dust Ash (SDA) - Fapohunda, C. A.; Amu, O. O.; Babarinde, O. F. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Availability of good soils for the construction of Civil engineering works is pivotal to the development and progress of any nation. Where good soils are lacking, it is necessary to make the soil fit through soil improvement methods. This study investigates the geotechnical performance of soil stabilized with the blend of cement and saw dust ash (SDA). The blend consists of 9% cement by weight and up to 10% of SDA at interval of 2%. The tests conducted on both stabilized and unstabilized soils samples at three different locations, identified as A, B, and C were: particle size distribution, natural moisture content, Atterberg’s limits, compaction, California Bearing Ratio (CBR) and Unconfined Compression Strength (UCS). The results showed decrease in plasticity index from high to medium, increase in CBR values: 4 – 10% for sample A, 2 – 12% for sample B and 5 – 8% for sample C, and increase in unconfined compression strength values: 45.23 – 65.88 kN/m2 for sample A, 34.01 – 59.18 kN/m2 for B and 41.80 – 63.94 kN/m2 for C. The results of this investigation showed that improvement of soil for construction purpose can be achieved when SDA is applied as a stabilizer in a cement-stabilized soil, up to 6% by weight of cement. Specifically, improved shear stress demonstrated up to 6% replacement is an indication of fitness for application of such soil in the design of footing, especially for columns, where shear stresses usually control the footing thickness.